2016
DOI: 10.18805/ijar.10981
|View full text |Cite
|
Sign up to set email alerts
|

Financial losses due to fertility problems in Anatolian Dairy Buffalo

Abstract: This study was performed to determine the financial losses due to fertility problems in Anatolian Dairy Buffaloes. The study material was lactation average values of Anatolian Dairy Buffalo. Age at first calving and calving interval were evaluated as fertility parameters. The financial losses relevant to one-day extension of these parameters were calculated. Bull cost was determined as per pregnancy, due to natural mating usually occurs in Anatolian Buffalo. The prices of calf, milk and feed were used in calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nevertheless, this strategy implies that primiparous water buffaloes must have an especial management to prevent anestrus and infertility and thus guarantee a short conception interval. Primiparity and calving during long photoperiod season affect negatively the reproductive performance (Hassan et al, 2017;El-Tarabany, 2018;Nava-Trujillo et al, 2018) and this affects negatively the herd's profitability (Cicek et al, 2017;Hassan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this strategy implies that primiparous water buffaloes must have an especial management to prevent anestrus and infertility and thus guarantee a short conception interval. Primiparity and calving during long photoperiod season affect negatively the reproductive performance (Hassan et al, 2017;El-Tarabany, 2018;Nava-Trujillo et al, 2018) and this affects negatively the herd's profitability (Cicek et al, 2017;Hassan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al [10] reported a decrease in economic return between 24 and 27% for water buffaloes with longer calving to conception interval; while the increase in the CI caused a decline in milk production of 2.1 kg per day when it increased from 365 to 635 days [9] and a negative correlation between CI and milk production per day of CI has been reported [18]. More recently, it was determined that the cost of each additional day of CI after 365 days, was 6.07 USD [23] and that each additional day over the average CI implies a decrease in earnings of 1.87 USD [24]. However, it is necessary to evaluate how reproductive strategies, like out-ofbreeding mating strategy, a practice to change the calving calendar, and increases milk offer during months with long photoperiod when water buffaloes have low reproductive activity [69], but this reproductive strategy produces a decrease of fertility and an increase of calving interval, affecting the economic performance of water buffalo systems.…”
Section: Economic Impact Of a Long Calving Intervalmentioning
confidence: 99%
“…Currently, livestock farmers need to recognize non pregnant animal at the earliest opportunity so as to rebreed them at the very next opportunity. In developing countries like India, buffaloes are the most important dairy animal but they are suffering from problems related to reproduction such as long calving intervals, long open period and high incidence of repeat breeding (Jamuna et al, 2015;Cicek et al, 2017). These problems further aggravates by lack of early pregnancy diagnosis tools.…”
Section: Introductionmentioning
confidence: 99%